A novel cost‐sensitive algorithm and new evaluation strategies for regression in imbalanced domains. Issue 4 (28th February 2021) - Sadouk, Lamyaa; Gadi, Taoufiq; Essoufi, El Hassan
Abstract: Many real‐world data mining applications involve obtaining predictive models using imbalanced datasets. Frequently, the least common target variables present within datasets are associated with events that are highly relevant for end users. When these variables are nominal, we have a class‐imbalance problem which has been thoroughly studied within machine learning. As for regression tasks where target variables are continuous, few predictive models and evaluation techniques exist. This paper proposes a solution to these challenges. First, we introduce a cost‐sensitive learning algorithm based on a neural network trained on the minimization of a biased loss function. Results show a higher or comparable performance and convergence speed to existent techniques. Second, we develop new approaches for performance assessment of regression tasks within imbalanced domains by proposing new scalar measures, namely Geometric Mean Error ( GME ) and Class‐Weighted Error ( CWE ), as well as new graphical‐based measures, namely REC TPR, REC TNR, REC G − Mean and REC CWA curves. Unlike standard measures, our evaluation strategies are shown to be more robust to data imbalance as they reflect the performance of both rare and frequent events.